2011
DOI: 10.1016/j.jpainsymman.2010.05.017
|View full text |Cite
|
Sign up to set email alerts
|

Fatigue and Functional Impairment in Early-Stage Non-Small Cell Lung Cancer Survivors

Abstract: Context Fatigue is the most common sequela among non-small cell lung cancer (NSCLC) survivors 1–6 years post-treatment and is associated with functional limitations. Objectives This study examined the prevalence, severity, and correlates of fatigue among early stage NSCLC survivors. Methods Three-hundred fifty individuals diagnosed and surgically treated for Stage IA or IB NSCLC completed a survey that included the Brief Fatigue Inventory (BFI) to assess the prevalence and severity of fatigue. The Self-Rep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
66
2
2

Year Published

2013
2013
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 77 publications
(74 citation statements)
references
References 65 publications
4
66
2
2
Order By: Relevance
“…Congruent with our results, other researchers found a significant negative relationship between symptom burden and functional status of advanced cancer patients [27][28][29][30][31] . In a recent study from Egypt that included patients with metastatic cancer, the total average ESAS score differed significantly according to the Eastern Cooperative Oncology Group (ECOG) performance scale from 34 in patients with an ECOG score of 1 to 70 in patients with an ECOG score…”
Section: Discussioncontrasting
confidence: 52%
See 1 more Smart Citation
“…Congruent with our results, other researchers found a significant negative relationship between symptom burden and functional status of advanced cancer patients [27][28][29][30][31] . In a recent study from Egypt that included patients with metastatic cancer, the total average ESAS score differed significantly according to the Eastern Cooperative Oncology Group (ECOG) performance scale from 34 in patients with an ECOG score of 1 to 70 in patients with an ECOG score…”
Section: Discussioncontrasting
confidence: 52%
“…In another study that included pancreatic cancer patients; pain, digestive symptoms, cachexia and ascites were significantly more likely to be reported by patients with an ECOG score of ≥1 29 . In lung cancer patients, moderate/severe fatigue is associated with significantly poorer PS 30 . This was confirmed in another study where there was a strong negative relationship between Karnofsky PS and the top four symptoms (pain, fatigue, disturbed sleep and distress) in lung cancer patients 31 .…”
Section: Esas Itemmentioning
confidence: 99%
“…It has been stated that the high level of fatigue despite the early stage of disease causes the impaired functional status of the patients. 65 It has been found that physical functioning of patients with advanced lung carcinoma decreased due to fatigue. The fatigue was not caused by weight loss and anemia but was related to psychological factors.…”
Section: Cancer-related Fatiguementioning
confidence: 99%
“…Prevalence rates for crf are reported to range from 70% to 100% during active treatment and to be about 30% in post-treatment survivors [1][2][3][4][5] . Although definitions of crf vary, elements include a subjective feeling of tiredness or exhaustion, prompted by cancer or treatment and disproportionate to the level of recent exertion, that is not relieved by rest and that interferes with usual daily activities 6,7 .…”
Section: Introductionmentioning
confidence: 99%